Biomarkers of epithelial-mesenchymal transition: E-cadherin and beta-catenin in malignant transformation of oral lesions - Yim, Ilena S; Laronde, Denise M (Canadian Journal of Dental Hygiene, 2024)
Detecting oral lesions at high risk of becoming cancer may enable early interventions to prevent oral cancer. The diagnosis of dysplasia in an oral lesion is used to predict this risk but is subject to interobserver and intraobserver variability. Studying biomarkers or molecular markers that reflect underlying molecular alterations can serve as an additional and objective method of risk assessment. E-cadherin and beta-catenin, molecular markers of epithelial-mesenchymal transition (EMT), potentially contribute to early malignant progression in oral tissue. This narrative review provides an overview of EMT, its relation to oral cancer, and the interaction among E-cadherin, beta-catenin, and the Wnt pathway in malignant progression of oral tissue. Full-text literature on EMT, E-cadherin, beta-catenin, oral epithelial dysplasia, and oral cancer was retrieved from PubMed and Google Scholar. Sixty original research articles, reviews, and consensus statements were selected for review. EMT, a biological mechanism characterized by epithelial and mesenchymal changes, can contribute to cancer development. Molecular markers of EMT including TWIST, vimentin, and N-cadherin may serve as prognostic markers of oral cancer. Dependent on Wnt pathway activity and the loss of membranous E-cadherin, E-cadherin and beta-catenin can play various roles along the spectrum of malignant progression, including tumour inhibition, early tumour progression, and late-stage tumour progression. Cross-sectional immunohistochemical research has found changes in expression patterns of E-cadherin and beta-catenin from normal oral tissue, oral epithelial dysplasia, to oral squamous cell carcinoma. Future research should explore the longitudinal role of EMT markers in predicting malignant progression in oral tissue.